Theory Organizational Behaviour untuk Menganalisa Pengaruh Psychological Well-Being dan Job Attitude terhadap Perawat Klinis - Ahmad Fauzi; Rina Anindita; Rokiah Kusumapradja (Syntax Corporation Indonesia, 2021)
Job Attitude nurses become the basis of the formation of good health services, one of the dimensions of job attitude is job satisfaction. Clear career development makes nurse job satisfaction good and has a loyalty impact on the hospital. Psychological well-being is the most important part of the nurse's Turn Over Intention process. The number of job demand nurses in daily activities causes job attitude nurses to be not good and nurses feel dissatisfied with high job demand. The goal is to analyze the effect of Job Demand and Career Development on The Job Attitude of Nurses In Class C Hospitals Through Psychological Well-being as an Intervening Variable. Research methods with an associative quantitative descriptive approach with cross-sectional research design. The data analysis technique used is path analysis and uses 63 nurses as a saturated sample of research. The result is the Effect of Job Demand and Career Development on Nurse Job Attitude Through Psychological Well-being as an Intervening Variable. Broadly speaking there is the Influence of Job Demand and Career Development on Job Attitude Through Psychological Well-being in Class C Hospital Tangerang City. Management must make a Determination of Work load of each nursing unit in the Hospital so that it can create a good assignment, plan the nurse's career development work program and make a corner of complaints so that every problem can be resolved properly. Further research needs to develop with a larger sample and add independent variables to be more widespread in the discussion